Analisis Pengendalian Piutang Tak Tertagih Terhadap Tunggakan Pembayaran Rekening Air Pelanggan Perusahaan Daerah Air Minum (PDAM) Tirtanadi Cabang Berastagi - Nurhayati, Nurhayati; Pohan, Salmia; Nursidin, Muhammad (Worksheet : Jurnal Akuntansi, 2023)
PDAM Tirtanadi is a company that operates in the service and provision of clean water for the community, especially in the city of Medan and also the Berastagi area. PDAM Tirtanadi's operations are financed through income received by PDAM Tirtanadi from customers who use PDAM Tirtanadi's services. However, the income received by PDAM Tirtanadi is not optimal due to the high level of arrears from PDAM Tirtanadi customers, especially at PDAM Tirtanadi Berastagi Branch, due to the decline in the community's economic income and the level of satisfaction of each customer regarding the company's performance in producing products that does not meet customer expectations, giving rise to delinquent behavior. This research aims to analyze the control of bad debts against customer water account payment arrears at the Tirtanadi Regional Drinking Water Company Berastagi Branch and to find out how effective it is in collecting receivables to convert them into cash. The analytical method used in this research is analysis of accounts receivable turnover, analysis of the average age of receivables.. The data collection technique used is primary data by conducting in-depth interviews with each informant and secondary data using literature, the internet, documentation. The data analysis technique used is descriptive qualitative.Keyword : Control, Bad Debt, Arrears.